1990
DOI: 10.1104/pp.92.3.802
|View full text |Cite
|
Sign up to set email alerts
|

Immunogold Localization of Ribulose-1,5-Bisphosphate Carboxylase with Reference to Pyrenoid Morphology in Chloroplasts of Synchronized Euglena gracilis Cells

Abstract: Euglena gracilis strain (Z) cells were synchronized under photoautotrophic conditions using a 14 hour light:10 hour dark regimen. The cells grew during the light period (growth phase) and divided during the following 10 hour period either in the dark or in the light (division phase). Changes in morphology of the pyrenoid and in the distribution of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) within the chloroplasts were followed by immunoelectron microscopy during the growth and division phases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…More recently, the form II Rubisco in the dinoflagellate Amphidinium also has been localized to pyrenoids (Jenks and Gibbs, 2000). Because the formation of pyrenoids in both Euglena (Osafune et al, 1990), which contains form I Rubisco, and Gonyaulax (Schmitter, 1971) is clock controlled, we reasoned that the form II Rubisco in Gonyaulax might be selectively sequestered into pyrenoids on a daily basis. Thus, we first determined whether Gonyaulax pyrenoids did, in fact, contain form II Rubisco.…”
mentioning
confidence: 99%
“…More recently, the form II Rubisco in the dinoflagellate Amphidinium also has been localized to pyrenoids (Jenks and Gibbs, 2000). Because the formation of pyrenoids in both Euglena (Osafune et al, 1990), which contains form I Rubisco, and Gonyaulax (Schmitter, 1971) is clock controlled, we reasoned that the form II Rubisco in Gonyaulax might be selectively sequestered into pyrenoids on a daily basis. Thus, we first determined whether Gonyaulax pyrenoids did, in fact, contain form II Rubisco.…”
mentioning
confidence: 99%
“…Details of the mechanism differ, however, as in Euglena the plastid-directed leader sequences contain two hydrophobic regions separated by an S/T-rich region reminiscent of a plastid transit sequence (Henze et al, 1995;Kishore et al, 1993). In vitro studies have demonstrated that the plastid directed proteins remain inserted in the ER membranes, unlike the apicomplexans where the plastid proteins are soluble inside the ER (Kishore et al, 1993;Osafune et al, 1990;Sulli et al, 1999;Sulli and Schwartzbach, 1996). The second hydrophobic region present in the Euglena leaders is absent in apicomplexan leaders (Foth et al, 2003).…”
mentioning
confidence: 99%
“…The grids were then floated on PBSwith 0.5% BSAcontaining antiserum or preimmune serum at 100-400 fold dilution for 20min at 37°C. The grids were then washed 5 times in PBS by flotation, and were then floated on PBS containing a 20-fold dilution of fifteen nm of protein Agold (E»Y Labs, USA) for 20min (6). The grids were subsequently floated on 3% (w/v) uranyl acetate for 10-20 min and after drying were viewed in a JEOL100B electron microscope at 80kV.…”
Section: Methodsmentioning
confidence: 99%